Modos de aplicação de zinco na nutrição e na produção de massa seca de plantas de trigo - Orioli Júnior, Valdeci [UNESP]; de Mello Prado, Renato [UNESP]; Luarte Leonel, Cristian [UNESP]; Amélio Cazetta, Disnei [UNESP]; Martoreli da Silveira, César [UNESP]; Barbosa Queiroz, Rafaela Josemara [UNESP]; Húngaro Aires da Gama Bastos, Joani Cristina [UNESP] (My University, 2008)
Zinc application methods can affect the nutrition and the initial development of the wheat. Thus, the aim of this work was to analyze the different ways of Zn application in the soil, on nutrition and on dry matter production. A completely randomized experimental design with four replications was used. The experiment was composed by the following Zn application treatments: control (no zinc application); soil incorporation, furrow located, seeds treatment and leaf pulverization. The experimental unit was composed of a pot filled with 7 L of soil. Morphological traits for each plant were determined on 52 days after emergence by the evaluations of plant height, internodes number, tillers number and aerial part dry matter. Still, the soil and plant chemical analysis was accomplished. The furrow located method provided larger concentrations of the micronutrient available. The zinc application methods did not influence the initial growth of the wheat plants. The zinc concentration in leaves was influenced by the different application methods, being the leaf pulverization the one that was caused the largest zinc accumulation on aerial part dry matter.
Methods of zinc application in the nutrition and production of wheat plant dry matter
Keywords: Application forms; Greenhouse; Micronutrient; Plants nutrition; Triticum aestivum L.